2021
DOI: 10.1016/j.bpobgyn.2021.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of vaccination in pregnancy

Abstract: Maternal immunisation is a public health strategy that aims to provide protection against certain infections to both mother and her foetus or newborn child. Vaccination of pregnant women induces vaccine-specific antibodies that lead to the subsequent transfer of these antibodies across the placenta or through breastfeeding to the offspring. At present, vaccinations in pregnancy are limited to pertussis, tetanus, diphtheria, polio, and the seasonal Influenza vaccine. Recently, some countries have incorporated r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 26 publications
2
44
0
4
Order By: Relevance
“…These results show a considerable improvement in vaccination adherence in comparison with data reported in Sicily by the Regional Health department due to the educational interventions conducted (<2.5% for DTPa and lower for influenza vaccination). In United Kingdom, during the 2018/2019 season, vaccine coverage in pregnant women against pertussis was higher than 70% and against flu was 45.2%, while in the US 61.2% of pregnant women received influenza vaccination during 2019/2020 season, rate similar to what observed in our sample after the educational interventions conducted [29].…”
Section: Discussionsupporting
confidence: 86%
“…These results show a considerable improvement in vaccination adherence in comparison with data reported in Sicily by the Regional Health department due to the educational interventions conducted (<2.5% for DTPa and lower for influenza vaccination). In United Kingdom, during the 2018/2019 season, vaccine coverage in pregnant women against pertussis was higher than 70% and against flu was 45.2%, while in the US 61.2% of pregnant women received influenza vaccination during 2019/2020 season, rate similar to what observed in our sample after the educational interventions conducted [29].…”
Section: Discussionsupporting
confidence: 86%
“…Argentina observed a relative reduction of 44% in the incidence of pertussis among children 2-6 months of age after it began vaccinating pregnant with Tdap in 2012 [81]. In the UK, the incidence of pertussis in infants <3 months of age declined overall from 234 per 100,000 in 2012 to 52 per 100,000 in 2019 [82]. At KPNC, incidence rates of pertussis among infants <1 year during 2010 to 2018 declined from more than 148/100,000 person-years to 25/100,000 personyears (Figure 2).…”
Section: Strategies With Successful Results: Maternal Tdap Vaccination During Pregnancymentioning
confidence: 99%
“…A recent survey among women in the US who were pregnant in 2018-2019 and delivered live-born infants reported that only 56% received a Tdap vaccine [87]. In the UK, in 2020, the average vaccine uptake was 70.5% [82]. We need strategies to increase vaccine uptake.…”
Section: Need To Increase Maternal Vaccination During Pregnancymentioning
confidence: 99%
“…Complications from influenza infections can also lead to pneumonia in children. Despite this, uptake of the influenza vaccine by pregnant women and in children up to 3 years of age remains relatively low, with coverage of approximately 44% in both populations [ 51 , 53 ].…”
Section: Discussionmentioning
confidence: 99%